The Immuno candies; Formulation, Characterization and Antioxidant Activity of Gotu Kola (Centella asiatica (L.) Urb) Herbal Hard Candy - Rafita Yuniarti; Minda Sari; Misna Rosalinda Hutabarat; Nurul Hasanah; Zulmai Rani (LPPM Universitas Abdurrab, 2024)
Background: Pagagan is a plant that has antioxidant properties. The benefits of antioxidants are essential for everyone because they can prevent cell damage due to the bad influence of free radicals. Formulating gotu kola in the form of candy is one effort so that the antioxidant effects of gotu kola can always be obtained easily because candy is a snack everyone likes and can be obtained easily anywhere. Objective: Formulate, physical characterization and antioxidant activity of hard candy immuno candies. Method: Hard candy formulation with varying concentrations of gotu kola herbal essence (0%, 1%, 5%, 10%, and 15%), physical characterization using organoleptic tests, water content, weight uniformity and stability, and antioxidant activity using the DPPH method. Results: Hard candy made with concentrations of 0%, 1%, 5%, 10%, and 15% has a sweet and slightly bitter taste (typical of gotu kola) at a concentration of 5%-15%, has a typical weak sugar aroma, and highwater content. respectively 0.72%, 0.77%, 0.84%, 0.8%, 0.89%, 0.95%, and is stable at a storage temperature of 8ºC-15ºC with closed packaging, has good weight uniformity, and IC50 values ​​were 32552.69 µg/mL, 12992.589 µg/mL, 12077.09 µg/mL 9669.15 µg/mL, 9484.519 µg/mL Conclusion: Gotu kola herbal juice can be formulated into hard candy up to a concentration of 15 %, has good physical characteristics as well as inactive antioxidant activity.